Irúsan : or, canting for architects - Drofiak, Nicholas (gta Verlag, ETH Zurich, 2020)
In 1931, architect Ivan Il’ic Leonidov was sent 2,800 kilometres northeast of Moscow to assist in constructing the new Soviet arctic port of Igarka. The city, though presented as an inscription of the future into the vast void of Siberia, in fact stood in the traditional territory of speakers of the indigenous language of Ket. Today spoken fluently by fewer than twenty people, the language isolate offers a grammatical model of reality unrelated to Indo-European language structures. This transdisciplinary work employs the Ket language as a medium of academic architectural discussion. It creates an encounter between Leonidov’s fantastical architectural drawings (The City of the Sun) and native Ket speaker and linguist Dr. Zoâ Vasil’evna Maksunova to reveal the uncertain, creative processes of hybrid isation, fictionmaking and translation as subjects and means of research practice. Linguistic theory is fused with historical eclecticisms to question diverse interpretations of Siberia, Igarka’s landscape and indigenous positionality. The work’s graphical elements and lyrical prose challenge conventional ways in which architectural history and knowledge are constructed.